2022
DOI: 10.3390/bioengineering9100527
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Polymorphism rs3025039 and Human T-Cell Leukemia Virus 1 (HTLV-1) Infection among Older Japanese Individuals: A Cross-Sectional Study

Abstract: Previous studies have reported a close correlation between vascular endothelial growth factor (VEGF), which plays an important role in angiogenesis, and human T-cell leukemia virus 1 (HTLV-1). However, an association between genetic characteristics related to VEGF and HTLV-1 infection has not yet been reported. Because the VEGF polymorphism rs3025039 is inversely associated with serum concentrations of VEGF, we focus on rs3025039 in the present study. To clarify the association between the VEGF polymorphism rs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In addition, in our previous study, genetic characteristics related to lower angiogenesis activity were revealed to be associated with a lower chance of establishing HTLV-1 infection [60]. Therefore, individuals with HTLV-1 infection might have higher angiogenesis activity than individuals without HTLV-1 infection, which prevents hypertension.…”
Section: Human T-cell Leukemia Virus Type 1 (Htlv-1) Structural Ather...mentioning
confidence: 88%
“…In addition, in our previous study, genetic characteristics related to lower angiogenesis activity were revealed to be associated with a lower chance of establishing HTLV-1 infection [60]. Therefore, individuals with HTLV-1 infection might have higher angiogenesis activity than individuals without HTLV-1 infection, which prevents hypertension.…”
Section: Human T-cell Leukemia Virus Type 1 (Htlv-1) Structural Ather...mentioning
confidence: 88%
“…Since 1990, much has been discussed about the relationship between genotypes and HTLV-1 disease progression ( 51 ). Until recent years many polymorphisms had been described as related to the progression of HTLV-1infection including human leucocyte antigen (HLA) genes ( 52 ), the immunoregulation-related gene FOXP3 ( 53 ), the vascular endothelial growth factor (VEGF) gene ( 54 ), Tax-responsive elements (TRE) gene ( 55 ), Mannose-binding lectin-associated serine protease 2 (MASP2) gene ( 56 ) and others that could be related to the pro-viral load control or development of clinical manifestations including HAM/TSP. In our in vitro model, the ACs, HAM/TSP, and ATLL patients donated only IgG antibodies, indicating that genetic factors related to any molecules other than the genes related to donnor’s IgG production could not influence the observed results.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the large number of HTLV-1 carriers worldwide, the safety of aflibercept for patients infected with HTLV-1 has not been explored in basic ophthalmologic studies. Numerous studies have demonstrated a relationship between HTLV-1 infection and VEGF (63)(64)(65)(66), which is a key factor in the pathogenesis of HU (67). One study reported the development of corneal endotheliitis in a patient infected with human herpesvirus-6 (HHV-6) after intravitreal injection of an anti-VEGF antibody (68).…”
Section: Discussionmentioning
confidence: 99%